Pertinencia académica de la carrera de Sociología-Utmach en relación a la inserción laboral de los graduados, periodo 2020-2022 - Flores Guerrero, Nikita Paulette; Gonzaga Alay, Roger Cristopher (Machala, 2024)
The present research explores the levels of relevance presented by the components of the curriculum project, curricular matrix, and micro curriculum and how this has affected the labour insertion of graduates of the Sociology career, therefore, the general objective was: to establish the relevance between the academic offer of the Sociology career – UTMACH and the job placement of graduates, period 2020-2022. The difficulties that sociologists present in finding employment according to their professional profile were considered. Unemployment demoralizes and generates a vicious circle where graduates are discouraged from continuing with studies, whether with master's degrees or diplomas, perceiving them as unprofitable. Likewise, the specific objectives focus on determining the curricular planning characteristics for the student’s professional formation of the Sociology degree, identifying the job placement opportunities that graduates have, and establishing the relevant management strategies for the job insertion of the graduates. Besides, it should be mentioned that the sociological foundation is Structural Functionalism, which understands educational institutions and student groups as social systems that participate in the same environment, differentiating themselves to work in specific functions. Regarding the epistemological approach of the study, it was empirical inductive; the research is positivist, that is, it seeks to establish patterns and causal laws through the collection and analysis of data in situ; the type of study is basic with a mixed methodology, since information is collected through surveys aimed at graduates of the Sociology Degree, interviews with employers, and experts in curriculum planning and design. The result obtained in the research determines that half of the graduates do not practice the profession; their workspaces are being occupied mostly by social workers, even though the career still maintains relevance and importance in the current context, since there are problems in sociologists’ academic formation, who present weaknesses in knowledge, skills, and competencies in specific areas of the field of Sociology. Consequently, it was identified that there are problems with academic formation, along these lines a proposal was prepared with the name of “Project to strengthen specific skills, and competencies of the profession to promote the labour insertion of graduates of the sociology career of the UTMACH", which is responsible for improving the competitive profile of sociologists, through the design of training workshops so that they master the techniques, tools and increase their knowledge, which will promote them in their professional itinerary; Its sociological foundation is Niklas Luhmann's systems theory, which explains how job placement is influenced by multiple interrelated factors, including academic formation and skills acquired during higher education, constituting a systematic operation of a social nature; For its part, the specific objectives of the proposal are to design workshops to strengthen professional skills in planning and/or the design of social plans, programs, and projects that expand job placement opportunities; to promote the mastery of computer software applicable to the systematization of empirical data and theoretical contrast related to the investigation of social phenomena, with the purpose of ensuring that professionals who graduated from the Sociology degree raise their quality of professional performance in their occupational fields. This will be done with the cooperation of the Sociology major and the authors of the research.
La presente investigación explora los niveles de pertinencia que presentan los componentes del proyecto, malla curricular, micro currículo y cómo estos inciden en la inserción laboral de los graduados de la carrera de Sociología, por lo tanto, se planteó como objetivo general: establecer la pertinencia entre la oferta académica de la carrera de Sociología – UTMACH y la inserción laboral de los graduados, periodo 2020-2022. Se tomó en consideración las dificultades que presentan los sociólogos para encontrar empleo de acuerdo a su perfil profesional, el desempleo desmoraliza, genera un círculo vicioso donde los egresados se desmotivan para continuar con estudios sea con maestrías o diplomados percibiéndolos como poco rentables. Asimismo, los objetivos específicos se enfocan en determinar las características de la planificación curricular para la formación profesional de los estudiantes de la carrera de Sociología, identificar las oportunidades de inserción laboral tienen los graduados y establecer las estrategias de gestión pertinentes para la inserción laboral de los graduados de la carrera. Además; se debe hacer mención que el fundamento sociológico es el Estructural funcionalismo, el cual entiende a las instituciones educativas y grupos estudiantiles como sistemas sociales que participan en un mismo ambiente diferenciándose para trabajar en funciones específicas. En cuanto al enfoque epistemológico del estudio fue empírico – inductivo; la investigación es de carácter positivista, es decir, busca establecer patrones y leyes causales a través de la recopilación y análisis de datos in situ; el tipo de estudio es básica con metodología mixta, puesto que se recoge información mediante encuestas dirigidas a los egresados de la Carrera de Sociología, entrevistas a empleadores, y expertos en planificación y diseño curricular. El resultado obtenido en la investigación determina que la mitad de los egresados no ejercen la profesión; sus espacios laborales están siendo ocupados en su mayoría por trabajadores sociales, a pesar de que la carrera aún mantiene pertinencia e importancia en el contexto actual, pues existen problemas en la formación académica de los sociólogos, quienes presentan debilidades en conocimiento, habilidades, y competencias en áreas específicas del campo de la Sociología. En consecuencia, se identificó que hay problemas con la formación académica, en esa línea se elaboró una propuesta con el nombre de “Proyecto de fortalecimiento de habilidades y competencias específicas de la profesión para promover la inserción laboral de graduados de la carrera de sociología de la UTMACH”, que tiene de responsabilidad lograr mejorar el perfil competitivo en los sociólogos, mediante el diseño de talleres de capacitación para que dominen los técnicas, herramientas y aumenten su conocimiento, que los impulsaré en su itinerario profesional; su fundamentación sociológica es la teoría de sistemas de Niklas Luhmann, que explica como la inserción laboral se ve influida por los múltiples factores interrelacionados, entre ellos, la formación académica y las habilidades adquiridas durante la educación superior, constituyendo una operación sistemática de carácter social; por su parte, los objetivos específicos de la propuesta es diseñar talleres de fortalecimiento en habilidades profesionales en planificación y/o diseño de planes, programas, y proyectos sociales que amplíen las oportunidades de inserción laboral; promover el dominio de software informáticos aplicables a la sistematización de datos empíricos y contrastación teórica relacionada con la investigación de fenómenos sociales, con el propósito de lograr que los profesionales egresados de la carrera de Sociología eleven su calidad en el desempeño profesional en sus campos ocupacionales. Esto se realizará con la cooperación de la carrera de Sociología y los autores de la investigación.
Keywords: PERTINENCIA ACADEMICA; INSERCION LABORAL; SOCIOLOGO; PLANIFICACION CURRICULAR